Application of mixture of exponentials distributions for modeling queuing systems - Šnipas , Mindaugas; Valakevičius, Eimutis (Lietuvos matematikos rinkinys, 2008)
The article considers approximation of positive distribution functions by mixture of exponentials distributions. This approximation enables to model non-markovian queuing systems by Markov process with continuous time and countable set of states.